Why some Minnesota Baptist youth depart from the faith of their families - Fiske, Ivan, 1955- (St. Louis, Missouri : Covenant Theological Seminary, 2009)
1 online resource (PDF (ix, 111 leaves)); Typescript (Photocopy); Includes abstract.; Thesis (D. Min.)--Covenant Theological Seminary, 2009; Bibliography: leaves 107-111